Interrelation between donor and recipient heart rates during exercise after heterotopic cardiac transplantation. - Yusuf, S (1985)
The interrelation between the rates of the innervated recipient heart and the denervated donor heart at rest, on standing, and during the different phases of maximal exercise was studied in nine patients 1-6 months after heterotopic cardiac transplantation. The resting heart rate was significantly higher in the donor heart compared with the recipient heart. Eight of the nine recipient hearts and none of the donor hearts showed an increase in heart rate on standing up. All patients were exercised using a Bruce protocol until fatigued. The increase in heart rate during the first three minutes of exercise was lower in the donor hearts (10.7(6) beats/min) than in the recipient hearts (30(4.8) beats/min) but the peak heart rates were almost identical (donor hearts 152.7(2.9) and recipient hearts 152(2.8) beats/min). Five of the nine donor hearts and none of the recipient hearts showed a significant increase in heart rate after cessation of exercise. Three minutes after exercise heart rate had decreased by only 0.2(5.7) beats/min in the donor hearts compared with 33.6(6) beats/min in the recipient hearts. In spite of these differences in response between the donor hearts and recipient hearts, there were significant correlations between the two heart rates in the same patient at rest, after the first three minutes of exercise, at peak exercise, and during recovery.